Digital currency and fiqh muasarah: exploring cryptocurrencies in Islamic finance / Amirah Elyana Shamsuddin … [et al.] - Shamsuddin, Amirah Elyana; Yusri, Atikah Nabilah; Abdul Moin, Nur Asyiqin; Mohamed Shaiful Azam, Nur Fatini; Sabri, Nur Huda Syazana (2023)
In recent times, cryptocurrencies have gained popularity and are employed for a variety of reasons. Instead of being used as a substitute for cash or as a means of commerce, people invest in Bitcoin and other cryptocurrencies for speculative purposes. Understanding how technology influences a monetary system through block chain, which leads to an overhaul of the global monetary system, is essential to comprehending cryptocurrencies and the digitization of money. Furthermore, online payments using digital currency started to gain popularity. The purpose of this currency's creation was to facilitate and secure payments. Transaction expenses arc reduced when blockchain technology is used. Because cryptocurrency transactions negatively affect Indonesia's financial system, monetary stability, and payment system, the government, through Bank Indonesia, has implemented a policy prohibiting them. Cryptocurrency is the advancement of financial technology that enables it to take the role of paper money in future financial transactions. In order to create laws that are compliant with the relevant legal order, it is hoped that in the future, the government and other stakeholders will take a deeper interest in the presence of bitcoin technology (Abd. Majid, M.S.,2021).